2021
DOI: 10.3390/microorganisms9091914
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ESBL-Producing Escherichia coli and Klebsiella pneumoniae Isolated from Clinical Samples in a Northern Portuguese Hospital: Predominance of CTX-M-15 and High Genetic Diversity

Abstract: Background: Enterobacteriaceae are major players in the spread of resistance to β-lactam antibiotics through the action of CTX-M β-lactamases. We aimed to analyze the diversity and genetic characteristics of ESBL-producing Escherichia coli and Klebsiella pneumoniae isolates from patients in a Northern Portuguese hospital. Methods: A total of 62 cefotaxime/ceftazidime-resistant E. coli (n = 38) and K. pneumoniae (n = 24) clinical isolates were studied. Identification was performed by MALDI-TOF MS. Antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
15
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 70 publications
6
15
3
Order By: Relevance
“…While bla CTX-M-15 is considered to be predominant, followed by bla CTX-M-14 , among our isolates, bla CTX-M-14 was more frequent than bla CTX-M-15 , in agreement with previously reported data from Spain [ 34 ] and China [ 35 ], which identified bla CTX-M-14 as the main ESBL in E. coli of adults with acquired UTIs. It may be noted that no acquired AmpC β-lactamase-producing E. coli were present in our collection, in agreement with a Portuguese study [ 36 ], performed with both clinical and non-clinical isolates [ 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While bla CTX-M-15 is considered to be predominant, followed by bla CTX-M-14 , among our isolates, bla CTX-M-14 was more frequent than bla CTX-M-15 , in agreement with previously reported data from Spain [ 34 ] and China [ 35 ], which identified bla CTX-M-14 as the main ESBL in E. coli of adults with acquired UTIs. It may be noted that no acquired AmpC β-lactamase-producing E. coli were present in our collection, in agreement with a Portuguese study [ 36 ], performed with both clinical and non-clinical isolates [ 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, E. coli isolates from clone ST131 belonged to the phylogenetic group B2. Other studies have shown that E. coli ST131/CTX-M-15/B2/ fimH30 is the most disseminated E. coli clonal group worldwide and that it contains an extensive antimicrobial resistance profile [ 36 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of antibiotic resistance is inseparable from the existence and spread of resistance genes. Our results show that bla TEM and bla SHV are present in mostly K. pneumoniae and bla CTX–M–15 is the main CTX-M gene detected, which is similar to the results of previous studies ( Timofte et al, 2014 ; Carvalho et al, 2021 ). These extended-spectrum β-lactamase (ESBL) resistance genes can lead to resistance by hydrolysis of penicillins and cephalosporins ( Algammal et al, 2020a ).…”
Section: Discussionsupporting
confidence: 92%
“…Two strains of ST23 K1 and ST23 K57 are characterized as hybrid hvKp-MDR. Thus, the data obtained in this study indicate the ongoing formation of hybrid K. pneumoniae on the base of the ST23 genetic line, which was already defined in the last decade [7,22,35,45].…”
Section: Discussionsupporting
confidence: 55%
“…All K. pneumoniae isolates carried bla SHV genes, including extended-spectrum beta-lactamase (ESBL) variant bla SHV-12 , broad-spectrum variants bla SHV-28 and bla SHV-33 , and narrow-spectrum variants bla SHV-67 and bla SHV-190 . These alleles of bla SHV genes were previously described in Portugal, Turkey, China, Russia, and Spain [ 22 , 35 , 36 ]. Three K. pneumoniae isolates (ST395 K47 , ST147 K64 , and ST23 K1 ) carried the bla TEM-1B , bla CTX-M-15 , and bla OXA-1 genes.…”
Section: Discussionmentioning
confidence: 99%